Temperature response of aquatic greenhouse gas emissions differs between dominant plant types. (1st November 2022) - Aben, Ralf C.H.; Velthuis, Mandy; Kazanjian, Garabet; Frenken, Thijs; Peeters, Edwin T.H.M.; Van de Waal, Dedmer B.; Hilt, Sabine; de Senerpont Domis, Lisette N.; Lamers, Leon P.M.; Kosten, Sarian
Highlights: The effect of experimental warming on GHG emissions differs between plant types. Emissions and response to warming were highest with algae and free-floating plants. CH4 ebullition was the GHG emission pathway most affected by experimental warming. Anticipated shifts in plant dominance may represent a positive climate feedback. Restoring submerged plant dominance may substantially mitigate GHG emissions. Abstract: Greenhouse gas (GHG) emissions from small inland waters are disproportionately large. Climate warming is expected to favor dominance of algae and free-floating plants at the expense of submerged plants. Through different routes these functional plant types may have far-reaching impacts on freshwater GHG emissions in future warmer waters, which are yet unknown. We conducted a 1, 000 L mesocosm experiment testing the effects of plant type and warming on GHG emissions from temperate inland waters dominated by either algae, free-floating or submerged plants in controls and warmed (+4 °C) treatments for one year each. Our results show that the effect of experimental warming on GHG fluxes differs between dominance of different functional plant types, mainly by modulating methane ebullition, an often-dominant GHG emission pathway. Specifically, we demonstrate that the response to experimental warming was strongest for free-floating and lowest for submerged plant-dominated systems. Importantly, our results suggest that anticipated shifts in plant type from submerged plants to a dominance of algae or free-floating plants with warming may increase total GHG emissions from shallow waters. This, together with a warming-induced emission response, represents a so far overlooked positive climate feedback. Management strategies aimed at favouring submerged plant dominance may thus substantially mitigate GHG emissions. Graphical abstract: Image, graphical abstract